If (a/cosec2)+(b/sec2)=c, prove that, cot2=(c-a)/(b-c)
Answers
Answered by
11
Answer refer to the attachment
Attachments:
![](https://hi-static.z-dn.net/files/dda/d4ed715cc60e8ac8ce0cd11ad76ba5a0.jpg)
Answered by
1
Given :-
─━─━─━─━─━─━─━─━─━─━─━─━─
To prove :-
─━─━─━─━─━─━─━─━─━─━─━─━─
─━─━─━─━─━─━─━─━─━─━─━─━─
Consider,
─━─━─━─━─━─━─━─━─━─━─━─━─
Additional Information:-
Relationship between sides and T ratios
sin θ = Opposite Side/Hypotenuse
cos θ = Adjacent Side/Hypotenuse
tan θ = Opposite Side/Adjacent Side
sec θ = Hypotenuse/Adjacent Side
cosec θ = Hypotenuse/Opposite Side
cot θ = Adjacent Side/Opposite Side
Reciprocal Identities
cosec θ = 1/sin θ
sec θ = 1/cos θ
cot θ = 1/tan θ
sin θ = 1/cosec θ
cos θ = 1/sec θ
tan θ = 1/cot θ
Co-function Identities
sin (90°−x) = cos x
cos (90°−x) = sin x
tan (90°−x) = cot x
cot (90°−x) = tan x
sec (90°−x) = cosec x
cosec (90°−x) = sec x
Fundamental Trigonometric Identities
sin²θ + cos²θ = 1
sec²θ - tan²θ = 1
cosec²θ - cot²θ = 1
Similar questions